Liver, Tumor and Viral Hepatitis: Key Players in the Complex Balance Between Tolerance and Immune Activation - Sällberg, Matti; Pasetto, Anna (Frontiers in Immunology, 2020)
Liver cancer is the third most common cause of cancer related death in the World. From an epidemiological point of view the risk factors associated to primary liver cancer are mainly viral hepatitis infection and alcohol consumption. Even though there is a clear correlation between liver inflammation, cirrhosis and cancer, other emerging liver diseases (like fatty liver) could also lead to liver cancer. Moreover, the liver is the major site of metastasis from colon, breast, ovarian and other cancers. In this review we will address the peculiar status of the liver as organ that has to balance between tolerance and immune activation. We will focus on macrophages and other key cellular components of the liver microenvironment that play a central role during tumor progression. We will also discuss how current and future therapies may affect the balance toward immune activation.